Determinants of Firm Value: Financial Performance, Capital Structure, and Corporate Governance in Emerging Markets - Soei Khim; Zul Azhar; Sri Mulyati; Syaharani Tiara Avrilia (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Firm value represents a central indicator of corporate success, particularly in emerging markets characterized by institutional uncertainty, weak external monitoring, and high information asymmetry. While prior studies have examined the roles of financial performance, capital structure, and corporate governance, empirical findings remain fragmented, largely due to methodological approaches that overlook hierarchical and mediating mechanisms. This study develops and tests a hierarchical and mediating structural model to explain firm value formation by integrating corporate governance, capital structure, and financial performance within a Partial Least Squares–Structural Equation Modeling (PLS-SEM) framework. Using secondary data from publicly listed non-financial firms in emerging markets, the analysis captures both direct effects and indirect transmission pathways among the constructs. The results demonstrate that financial performance functions as the primary transmission mechanism, exerting the strongest direct effect on firm value while simultaneously mediating the influence of corporate governance. Corporate governance shows a substantial impact on financial performance and a complementary direct effect on firm value, indicating that governance enhances market valuation largely through performance improvement. In contrast, capital structure exhibits a weaker and context-dependent effect, suggesting that excessive leverage may undermine firm value in volatile emerging market environments. Overall, the model exhibits strong explanatory power, confirming the relevance of a hierarchical SEM-PLS approach in uncovering firm value formation mechanisms. This study contributes to corporate finance literature by clarifying how governance structures translate into firm value through financial performance, offering both theoretical refinement and practical insights for managers, investors, and policymakers in emerging markets.   Keywords: Firm value; Financial performance; Capital structure; Corporate governance; Emerging markets; PLS-SEM